The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fimmu.2018.02937
|View full text |Cite
|
Sign up to set email alerts
|

Defective Autophagy in T Cells Impairs the Development of Diet-Induced Hepatic Steatosis and Atherosclerosis

Abstract: Macroautophagy (or autophagy) is a conserved cellular process in which cytoplasmic cargo is targeted for lysosomal degradation. Autophagy is crucial for the functional integrity of different subsets of T cells in various developmental stages. Since atherosclerosis is an inflammatory disease of the vessel wall which is partly characterized by T cell mediated autoimmunity, we investigated how advanced atherosclerotic lesions develop in mice with T cells that lack autophagy-related protein 7 (Atg7), a protein req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 50 publications
(68 reference statements)
1
18
0
Order By: Relevance
“…In previous studies, IRGM/Irgm1 was found to play a critical role in IFN-γ-induced autophagy (41,42). It has been reported that IRGM/Irgm1 can promote macrophage autophagy and inhibit the activation of inflammasome NLRP3, thereby protecting the intestine from inflammatory attack (39,43).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In previous studies, IRGM/Irgm1 was found to play a critical role in IFN-γ-induced autophagy (41,42). It has been reported that IRGM/Irgm1 can promote macrophage autophagy and inhibit the activation of inflammasome NLRP3, thereby protecting the intestine from inflammatory attack (39,43).…”
Section: Discussionmentioning
confidence: 95%
“…The pioneer of atherosclerotic inflammation theory, Peter Libby, pointed out very early that inflammation starts from the recruitment of white blood cells and secretion of proinflammatory factors in the early stage of atherosclerosis and is involved in the entire process of the disease (36). The CANTOS study published in 2017 revealed that the administration of IL-1β monoclonal antibody canakinumab could provide a significant In previous studies, IRGM/Irgm1 was found to play a critical role in IFN-γ-induced autophagy (41,42). It has been reported that IRGM/Irgm1 can promote macrophage autophagy and inhibit the activation of inflammasome NLRP3, thereby protecting the intestine from inflammatory attack (39,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a model of inflammatory bowel disease, mice bearing ATG16L1-deficient T cells develop a more severe disease with increased T helper (Th)2 differentiation and reduced regulatory T cell (Treg) generation, with no major alterations on Th1 and Th17 populations (Kabat et al, 2016). On the other hand, in a mouse model of diet induced steatosis, ATG7-deficient T cells show increased expression of IFN ɣ and IL-17 in both CD4+ and CD8+ T cells, suggesting differentiation bias toward Th1 and Th17 phenotypes in CD4+ T cells (Amersfoort et al, 2018). Furthermore, through regulated degradation of the transcription factor PU.1, autophagy has also been shown to limit Th9 differentiation, and T cells deficient in ATG3 or ATG5 show increased IL-9 production and improved IL-9-mediated tumor control (Rivera Vargas et al, 2017).…”
Section: Functions Of Autophagy In T Cellsmentioning
confidence: 99%
“…A recent study reported decreased atherosclerosis in mice with autophagy-related protein ( Atg7 ) deletion in T cells. 10 The atheroprotective effect could not be attributed to a reduction of T-cell–mediated inflammation because Atg7 -deficient T cells produced higher levels of the proatherogenic IFN (interferon)-γ. Htowever, Atg7 deficiency in T cells was associated with an unexplained reduction of plasma cholesterol levels, which may have accounted for the atheroprotective effects. Given that dysfunctional autophagy may impair T helper cell differentiation, effector cell activation 11 and anergy, 12 memory formation, 13 as well as regulatory T-cell (Treg) responses, 14 addressing the role of autophagy in selective T-cell subsets is necessary for a better understanding of the relevance of those processes to atherogenesis.…”
mentioning
confidence: 99%